CLINICAL OUTCOME OF STEINDLER FLEXORPLASTY AND SAHA PROCEDURE IN TREATING SUPERIOR TRUNK BRACHIAL PLEXUS INJURY - Muhammad Hadyan Syahputra; Nur Rachmat Lubis; Davin Setiamanah Caturputra (Majalah Kedokteran Sriwijaya, 2022)
Abduction is the most important functional movement of the glenohumeral joint, and at the same time one of the most complex movements of the entire body. Brachial plexus injury can make shoulder fail to abduction. Saha’s procedure (trapezius transfer) one procedure that safe and significantly improve the shoulder movement especially abduction. We report a teenager male presented with inability to move his right shoulder and elbow after a motor vehicle accident 5 weeks before. He was unable to move the elbow and shoulder, but the hand and wrist still had a good function. From the right shoulder X-Ray there is proximal humerus fracture. Steindler flexorplasty was performed after 3 months strengthening program. 6 months after Steindler flexorplasty, Saha’s procedure was performed to improve the shoulder movement. The shoulder can abduction 200-550 and the elbow can flex 200-800 after the surgery. In this case, the superior trunk of the brachial plexus was injured due to the shoulder and the neck forcibly widens after direct shoulder trauma. Saha’s procedure after Steindler flexorplasty is best for superior trunk brachial plexus injury, a simple procedure with minimal blood loss, which provided functional improvement. Steindler flexorplasty and Saha’s Procedure are two procedures very beneficial to the patients who experienced superior trunk brachial plexus injury.